3PC-003 Weight-lowering pseudoephedrine-based prescriptions: monitoring patient feedback after update of national price list of medicines and magistral preparation. (March 2019) - Pirrone, A; Marangon, V; Nisic, AA; Panzeri, F; Cavallo, L; Manfredi, AL; Palmieri, G; Pizzonia, MG; Avantaggiato, M
Abstract : Background: The decree 27/07/2017 of the Ministry of Health allow the prescription and dispensation in private pharmacies of weight-lowering magistral preparations containing pseudoephedrine. The commercially available pharmaceutical equivalent is unsuitable. Meanwhile, on 9 November 2017, the National Price List of Medicines and Magistral Preparation (NPM) was updated. Among several changes introduced, the price of magistral preparations were increased by 40% in order to offset additional charges related to general, preliminary and subsequent professional activities linked to preparation and dispensation. The hospital pharmacist, operating in the local pharmaceutical services, guarantees the appropriate supervision of these prescriptions. Purpose: To evaluate whether the price change, due to update of the NPM, has affected the number of prescriptions and patients considering a territorial pharmaceutical service. Material and methods: The number of prescriptions, patients and price of preparations, and other data regarding prescriptions have been collected using Microsoft Excel. Period analysis according to date of dispensation: from 1 September 2017 to 11 August 2018, divided into five 69 day periods (from P1 to P5), of which one was prior and four after 9 November 2017. Results: In the analysed period, from 1 September 2017 to 11 August 2018, 1671 prescriptions were dispensed, referring to 442 patients from 17 different pharmacies. The average number of patients treated per period was 159. P1: 236 preparations, 158 patients, average price €16.79. P2: 321 preparations, 170 patients, average price €30.35. P3: 310 preparations, 148 patients, average price €31.52. P4: 343 preparations, 147 patients, average price €31.98. P5: 461 preparations, 184 patients, average price €31.63. Conclusion: The average price between the first and fifth period has increased by 88%. Despite the substantial increase in price, there has not been a substantial variation in the number of dispensations and patients treated, underlining that the pharmacist's professionalism and his galenic skills can compensate for the lack of suitable commercially available pharmaceutical equivalents. References and/or acknowledgements: Law 94/1998, Decree 27/07/2017 of the Ministry of Health, Decree 22/09/2017 of the Ministry of Health. No conflict of interest.